2013
DOI: 10.1186/1471-2458-13-460
|View full text |Cite
|
Sign up to set email alerts
|

The potential for multi-disciplinary primary health care services to take action on the social determinants of health: actions and constraints

Abstract: BackgroundThe Commission on the Social Determinants of Health and the World Health Organization have called for action to address the social determinants of health. This paper considers the extent to which primary health care services in Australia are able to respond to this call. We report on interview data from an empirical study of primary health care centres in Adelaide and Alice Springs, Australia.MethodsSixty-eight interviews were held with staff and managers at six case study primary health care service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 24 publications
(27 reference statements)
4
74
0
2
Order By: Relevance
“…As an NGO they haddid, however, have some flexibility not available to the state-managed services the ability to provide services outside the scope of the service agreement, giving them some flexibility not available to the state-managed services. The more positive findings for the community controlled and non-government organisations accord with our findings of strengths for these two models in other aspects of CPHC as well, such as health promotion, action on the social determinants of health, and community participation Baum et al, 2013;Freeman et al, 2014). These findings support literature indicating more comprehensive models of PHC only achieve traction outside the mainstream health system (Hurley et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As an NGO they haddid, however, have some flexibility not available to the state-managed services the ability to provide services outside the scope of the service agreement, giving them some flexibility not available to the state-managed services. The more positive findings for the community controlled and non-government organisations accord with our findings of strengths for these two models in other aspects of CPHC as well, such as health promotion, action on the social determinants of health, and community participation Baum et al, 2013;Freeman et al, 2014). These findings support literature indicating more comprehensive models of PHC only achieve traction outside the mainstream health system (Hurley et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…Improving health care access and reducing health inequities are key objectives of CPHC (Baum, 2007;World Health Organization, 1978) and require a broad range of strategies enabling actions on social determinants of health inequity (Baum et al, 2013; Commission on Social Determinants of Health, 2008), and enhancing equity of access (Freeman et al, 2011;Thiede et al, 2007). These strategies require funding, organisational and policy support, which are vulnerable to changes in fiscal and political environments (Hanratty et al, 2007;Jolley et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, workers in state-managed services were taking IAH within less supportive organisational environment, and the constraints to their political agency from their role as public servants had increased as the priorities of the Department of Health had shifted away from health promotion. 30 This research offers a largely historical review as health promotion work has recently largely been removed from South Australian health services.…”
Section: Discussionmentioning
confidence: 99%
“…These included an Aboriginal community controlled organisation, Central Australian Aboriginal Congress, a non-government agency, the Sexual Health information networking and education SA Inc (SHine SA), and four South Australian state-government-managed services anonymised as Services A, C, D, and E. 30 Service B withdrew from the study prior to the research reported here and was replaced by Service E. Such turnover was expected as the project spanned five years at a time of considerable change and reorganisation of PHC within Australia. Service labels were maintained for consistency across the project research papers.…”
Section: Methodsmentioning
confidence: 99%
“…Published literature on the topic is mostly theoretical or commentary, with the very few studies in small and atypical practice settings. [2][3][4][5][6][7][8][9][10] The article by DeVoe and colleagues in this issue of Annals recommends a very reasonable approach of collecting community and patient data before taking individual patient and panel actions and then adding automated supports. 11 Before we ask practices to take on these tasks, however, we need much more evidence that it is both feasible and effective.…”
mentioning
confidence: 99%